Increase in Cell Wall Thickening and Biomass Production by Overexpression of PmCesA2 in Poplar - Maleki, Samaneh Sadat; Mohammadi, Kourosh; Movahedi, Ali; Wu, Fan; Ji, Kong Shu (Frontiers in Plant Science, 2020)
Abstract Cellulose, the most abundant constituent material of the plant cell walls, is a major structural component of plant biomass. Manipulating cellulose synthesis (CesA) genes by genetic engineering technology, to increase cellulose production may thus offer novel opportunities for plant growth and development. To investigate this, here we produced transgenic “Populus 895 plants” overexpressing the cellulose synthase (CesA2) gene derived from Pinus massoniana under the control of constitutive 35S promoter, via Agrobacterium-mediated transformation. Relative expression levels of PmCesA2 were functionally characterized in poplar hybrid clone “Nanlin895” (Populus deltoides × P.euramericana). The results demonstrated the transgenic lines showed enhanced growth performance with increased biomass production than did the untransformed controls. It is noteworthy that the overexpression of PmCesA2 in poplar led to an altered cell wall polysaccharide composition, which resulted in the thickening of the secondary cell wall and xylem width under scanning electron microscopy. Consequently, the cellulose and lignin content were increased. Hence, this study suggests that overexpression of PmCesA2 could be used as a potential candidate gene to enhance cellulose synthesis and biomass accumulation in genetically engineered trees.